Improving the First Year Students’ Reading Comprehension Achievement by Using SQ3R Technique at SMA Negeri 1 Jember - Ahmad Ridho Rojabi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2013)
This study aimed to improve the reading ability of first-year students at SMA Negeri 1 Jember by implementing the SQ3R technique, particularly in narrative texts. To achieve this goal, classroom action research was conducted in collaboration with the first-year English teacher, following several stages: planning, implementation, observation, and reflection. The research was implemented in two cycles, with each cycle consisting of four meetings. The SQ3R technique comprises five steps: survey, question, read, recite, and review. The survey and question steps were implemented in pre-learning, the reading step in whilst-learning, and the recite and review steps in post-learning. Penelitian ini bertujuan untuk meningkatkan kemampuan membaca siswa kelas satu SMA Negeri 1 Jember dengan mengimplementasikan teknik SQ3R terutama dalam teks narasi. Untuk mencapai tujuan tersebut, penelitian tindakan kelas berkolaborasi dengan guru bahasa Inggris kelas satu dengan mengikuti beberapa tahapan: perencanaan, implementasi, observasi, dan refleksi. Penelitian diimplementasikan dalam dua siklus, di mana setiap siklus mencakup empat pertemuan. Teknik SQ3R terdiri dari lima tahapan: survey, question, read, recite, dan review. Tahap survey dan question diimplementasikan di pre-learning, tahap membaca diimplementasikan di whilst-learning, sedangkan recite dan review diimplementasikan di post-learning.